The influence of the development of small and medium enterprises on economic growth in the SME sector in Indonesia - Ade Raselawati (Institute of Accounting Research and Novation (IARN), 2022)
The role of Small and Medium Enterprises (SMEs) in accelerating economic growth is very important, this can be seen from their contribution to the balance of payments through export activities and their ability to absorb a large number of workers, namely 70% of the total workforce in Indonesia. This study aims to analyze the influence of the development of Small and Medium Enterprises (SMEs) on economic growth in the SME sector in Indonesia. In this study used the panel data method with the Fixed Effect Model. The data used are secondary data in the form of SME GDP, SME workforce, SME exports, number of SME units, and SME investment from 2000-2009. The results of the analysis using the panel data regression method show that SME exports, the number of SME units, and SME investment has a positive and significant effect on economic growth in the SME sector. Meanwhile, the SME workforce variable has no significant effect on economic growth in the SME sector because the labor absorbed is not proportional to the added value generated.